Aerogel-based anti-condensation coating

By using aerogel and modified hollow glass microbeads in anti-condensation coatings, the problems of short initial dew point and difficult to control the condensation amount in existing coatings in extreme environments are solved, and efficient and lasting in industrial environments are achieved Anti-condensation effect.

CN119119795APending Publication Date: 2024-12-13NEWARD COMPOSITE BUILDING MATERIALS (SHANGHAI) CO LTD
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202411300132.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

When faced with an environment where the temperature difference between day and night is drastically changed or the temperature of the cold fluid is extremely low, the initial dew point is short and the amount of condensation is difficult to control, making it difficult to meet the high standards of industrial applications.

Method used

Using aerogel-based anti-condensation coating, the insulating glass microbeads are formed by introducing aerogel and hollow glass microbeads into the coating, especially hollow glass microbeads modified by fluorinated acrylate and polyN-isopropyl acrylamide surface. Synergistic effect improves the thermal insulation and insulation properties of the paint, extends the initial dew point time and reduces the amount of dew condensation.

Benefits of technology

It significantly improves the anti-condensation performance of the paint, maintains stable performance in a wider temperature range, extends the initial dew point time and strictly controls the amount of condensation, and is suitable for complex and changeable industrial environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005047394440000041
    Figure BDA0005047394440000041
  • Figure BDA0005047394440000051
    Figure BDA0005047394440000051
  • Figure BDA0005047394440000082
    Figure BDA0005047394440000082
Patent Text Reader

Abstract

The invention relates to the technical field of building coatings, in particular to an aerogel-based anti-condensation coating. The aerogel-based anti-condensation coating is prepared from the following components in percentage by weight: 30 percent to 45 percent of deionized water, 0.1 percent to 1.0 percent of cellulose, 5 percent to 10 percent of powder, 25 percent to 35 percent of emulsion, 0.5 percent to 3.0 percent of aerogel, 15 percent to 30 percent of hollow glass beads and 1 percent to 2 percent of auxiliaries. By introducing the aerogel and the hollow glass beads, especially the hollow glass beads subjected to surface modification by fluorinated acrylate and poly (N-isopropylacrylamide), the anti-condensation performance of the coating is remarkably improved, and the characteristics of high specific surface area and low density of the aerogel are remarkably improved; according to the present invention, the coating material can maintain the excellent anti-condensation effect in the wide temperature range (including the rapid change of the day and night temperature difference and the extremely low cold fluid temperature environment) under the combined action of the hollow structure of the hollow glass bead and the low wettability after the modification, such that the initial dew point time is substantially prolonged, and the condensation amount is strictly controlled to the low level.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of architectural coatings, and in particular to an aerogel-based anti-condensation coating. Background Art

[0002] In the vast fields of modern architecture and industry, condensation is a stubborn problem that frequently occurs in environments with high humidity and significant temperature differences, such as basements, storage spaces, cold storages, and industrial plants. In these places, condensation is particularly serious, which not only causes moisture and mildew on the walls and equipment surfaces, affecting visual beauty and sanitation, but also poses a potential threat to the safety of building structures, the operating efficiency of equipment, and long-term service life.

[0003] In view of the above challenges, the industry has generally adopted protective measures such as spraying anti-condensation coatings on key facilities such as cryogenic storage tanks, medical cooling devices, and cold fluid delivery pipelines. However, the anti-condensation coatings currently on the market still have limitations in performance. Their initial dew points are generally short, mostly between 30 and 60 minutes, and the condensation amount is not well controlled, often exceeding 5 grams. When faced with extreme working conditions such as drastic changes in temperature between day and night or extremely low cold fluid temperatures (below 0°C), the anti-condensation effect of these coatings is often greatly reduced, making it difficult to meet the high standards required for industrial applications.

[0004] Therefore, developing more efficient and durable anti-condensation coatings to cope with complex and changing industrial environments has become an urgent issue to be addressed. Summary of the invention

[0005] In order to solve the above-mentioned problems, the present application provides an aerogel-based anti-condensation coating, which aims to significantly improve the anti-condensation performance of the coating, effectively extend the initial dew point time, and strictly control the condensation amount to a lower level.

[0006] The aerogel-based anti-condensation coating provided in this application adopts the following technical solution: An aerogel-based anti-condensation coating comprises, by weight percentage, 30-45% deionized water, 0.1-1.0% cellulose, 5-10% powder, 25-35% emulsion, 0.5-3.0% aerogel, 15-30% hollow glass microspheres and 1-2% additives.

[0007] By adopting the above technical solution: the coating can still show excellent anti-condensation effect when facing extreme working conditions such as sharp changes in temperature between day and night or extremely low temperature of cold fluid (below 0°C). This is due to the dual effects of aerogel and hollow glass microspheres, which enable the coating to maintain stable performance in a wider temperature range; The aerogel-based anti-condensation coating achieves efficient and lasting anti-condensation effects in complex and ever-changing industrial environments through unique formula design and component ratio, providing strong support for solving the condensation problem in modern construction and industrial fields.

[0008] Analyzing the reasons, it may be: As a nanoporous material, aerogel has extremely low thermal conductivity, which can effectively prevent heat from being transferred through the coating. In anti-condensation coatings, it can significantly reduce the overall thermal conductivity of the coating, thereby slowing down or preventing condensation caused by temperature differences. Its high specific surface area and nanoporous structure enable it to form a continuous insulation layer in the coating, effectively isolating the influence of external heat on the substrate, maintaining the surface temperature of the substrate stable, and reducing the occurrence of condensation.

[0009] At the same time, the interior of the hollow glass microspheres is filled with air, which makes the microspheres have extremely low thermal conductivity, can increase the volume density and surface roughness of the coating, help form a more stable air layer, and further reduce heat transfer and condensation.

[0010] Aerogel and hollow glass beads work together in the coating to form a synergistic effect. Aerogel provides a continuous insulation layer, while hollow glass beads further enhance the thermal insulation and anti-condensation properties of the coating through their hollow structure and spherical characteristics. When curing into a film, aerogel and hollow glass beads can be evenly distributed in the coating to form a dense insulation network, which can not only effectively prevent the transfer of heat, but also improve the overall strength and durability of the coating.

[0011] Preferably, the components, measured by weight percentage, include: 30-35% deionized water, 0.1-0.5% cellulose, 5-10% powder, 25-30% emulsion, 1.5-3.0% aerogel, 15-25% hollow glass microspheres, and 1-2% additives.

[0012] By adopting the above technical solution: the performance of aerogel-based anti-condensation coating will be further improved.

[0013] Preferably, the components, by weight percentage, include: 35% deionized water; 0.5% cellulose; Powder 5%; emulsion 30%; aerogel 2.5%; hollow glass microspheres 25%; additives 2%.

[0014] By adopting the above technical solution: the aerogel-based anti-condensation coating prepared by the formula of this specific component can show efficient and long-lasting anti-condensation effect in complex and changeable industrial environments. It can not only cope with extreme temperature differences, but also maintain stable performance in low temperature environments.

[0015] Preferably, the hollow glass microspheres are hollow glass microspheres that are surface-modified with fluorinated acrylate and poly (N-isopropylacrylamide).

[0016] By adopting the above technical solution: the introduction of fluorinated acrylate may further reduce the thermal conductivity of the microsphere surface, because fluoride generally has lower surface energy and higher thermal stability, and the fluorinated group has extremely strong hydrophobicity, which can significantly reduce the wettability of the microsphere surface, which means that in a humid environment, the microsphere surface is less likely to be wetted by water, thereby reducing the possibility of condensation; At low temperatures, poly (N-isopropylacrylamide) (PNIPAM segments) may be more stretched and hydrophilicity may be enhanced; at high temperatures, the segments may shrink and hydrophilicity may be weakened. Adjusting the distribution of PNIPAM segments and thus changing the wetting state of the coating surface can help improve the anti-condensation performance of the coating to a certain extent. Therefore, the surface modification of hollow glass microspheres using fluorinated acrylate and PNIPAM can significantly improve the anti-condensation performance of aerogel-based anti-condensation coatings.

[0017] Preferably, the specific preparation steps of the hollow glass microsphere modification include: S1. placing hollow glass microspheres in a plasma reactor and introducing fluorinated acrylate vapor. Under the action of plasma, monomer molecules are excited and polymerized, and deposited on the surface of the microspheres; S2. After the surface polymerization deposition of the fluorinated acrylate is completed, the modified hollow glass microspheres are taken out from the plasma reactor and preliminarily cleaned to remove unreacted monomers and byproducts on the surface; S3, then re-dispersing the microbeads in an aqueous solution of methanol to form a stable suspension, then adding a certain amount of poly (N-isopropylacrylamide) solution to the suspension to ensure that the poly (N-isopropylacrylamide) can be evenly dispersed and contacted with the surface of the microbeads modified by the fluorinated acrylate to form a mixed solution, then heating the mixed solution and continuously stirring, keeping the temperature for reaction for 2.5-3 hours, and then post-treating to obtain; The feeding ratio of the hollow glass microspheres to the fluorinated acrylate and poly (N-isopropylacrylamide) is 1:(0.24-0.26):(0.51-0.55) by mass ratio.

[0018] By adopting the above technical solution: the prepared modified hollow glass microspheres have excellent anti-condensation performance and have broad application prospects and market value.

[0019] Preferably, the cellulose is one or more of hydroxypropyl methylcellulose, hydroxyethyl methylcellulose, methylcellulose, hydroxyethyl cellulose, and carboxymethyl cellulose.

[0020] By adopting the above technical solution: combining one or more of the above cellulose types, their respective advantages can be fully utilized to achieve complementary and optimized performance to meet certain requirements of the product for anti-condensation performance.

[0021] Preferably, the powder is one or more of carbonate powder, silicate powder, sulfate powder, metal and oxide powder, and special functional powder.

[0022] By adopting the above technical solution: using different types of powders in combination, their respective advantages can be comprehensively brought into play to achieve complementary and optimized performance.

[0023] Preferably, the emulsion is one or more of styrene acrylic emulsion, acrylic emulsion, silicone acrylic emulsion, fluorocarbon emulsion, chloroform emulsion, silicone resin emulsion, waterborne polyurethane resin emulsion, and tert-acrylic emulsion.

[0024] By adopting the above technical scheme: using one or more of styrene acrylic emulsion, acrylic emulsion, silicone acrylic emulsion, fluorocarbon emulsion, chloroformic emulsion, silicone resin emulsion, water-based polyurethane resin emulsion, and tert-propylene emulsion as the emulsion component in the formula, the performance of the product can be significantly improved, the application field can be broadened, the construction efficiency and quality can be improved, and the durability and stability of the product can be enhanced.

[0025] Preferably, the aerogel is prepared by dispersing aerogel powder material in water, wherein the specific surface area of ​​the aerogel powder material is 500-800m 2 / g, a density of 0.08-0.1g / ml, a particle size of 0.01-1mm, and at least one of silica aerogel, alumina aerogel, graphene-titania aerogel, and silica-alumina composite aerogel.

[0026] By adopting the above technical solution: aerogel prepared from aerogel powder materials of specific specifications can significantly improve the anti-condensation performance of coatings, mainly due to its high specific surface area, low density, suitable particle size and diverse composition selection. These characteristics work together to make aerogel an ideal additive to improve the anti-condensation performance of coatings.

[0027] Preferably, the auxiliary agent includes one or more of a dispersant, a wetting agent, a defoaming agent, a pH regulator, and a film-forming auxiliary agent.

[0028] By adopting the above technical solution: selecting the above-mentioned additives, the processing performance, construction performance and performance of the final product of the epoxy resin composition can be significantly improved. These additives play an indispensable role in the epoxy resin composition and are an important component for preparing high-performance epoxy resin compositions.

[0029] In summary, the present application includes at least one of the following beneficial technical effects: 1. The coating significantly improves the anti-condensation performance of the coating by introducing aerogel and hollow glass microspheres, especially the hollow glass microspheres modified with fluorinated acrylate and poly-N-isopropylacrylamide. The high specific surface area and low density characteristics of aerogel, as well as the hollow structure and low wettability of the hollow glass microspheres after modification, enable the coating to maintain excellent anti-condensation effect in a wider temperature range (including environments with drastic changes in temperature between day and night and extremely low cold fluid temperatures), which greatly prolongs the initial dew point time and strictly controls the condensation amount to a lower level; 2. The coating formula has been carefully designed. The synergistic effect between the components enables the coating to perform well in complex and changeable industrial environments. In environments with large humidity changes, the coating can maintain stable performance and effectively prevent the occurrence of condensation. At the same time, the emulsion ingredients such as styrene acrylic emulsion and acrylic emulsion not only improve the performance of the coating, but also enhance its durability and stability, thereby extending the service life of the coating. DETAILED DESCRIPTION

[0030] The present application is further described in detail below in conjunction with the examples. Except for the special instructions below, the raw materials used in the present application are all common commercially available materials. Performance Testing The anti-condensation performance of the prepared aerogel-based anti-condensation coating was tested according to the test standard HG / T 4560-2013 "Test method for anti-condensation performance of coatings".

[0031] Preparation Example Preparation Example 1 A hollow glass microsphere is prepared by surface modification of hollow glass microspheres with fluorinated acrylate and poly-N-isopropylacrylamide, wherein the hollow glass microspheres are selected from 3M TM Hollow glass microsphere K15, the specific preparation method is as follows: S1. First, 50 kg of hollow glass microspheres were placed in a plasma reactor and pre-evacuated to -0.4 MPa, and then 12.5 kg of fluorinated acrylate vapor was slowly introduced; Under the action of the plasma generator, high-energy plasma is generated inside the reactor, colliding with the fluorinated acrylate monomer molecules, stimulating their activity, and thus initiating a polymerization reaction. During this process, the fluorinated acrylate monomer molecules gradually polymerize on the surface of the microspheres to form a uniform and dense polymer layer. S2. After the surface modification deposition of the fluorinated acrylate is completed, the reactor is allowed to cool naturally to room temperature, and then the modified hollow glass microspheres are taken out of the reactor and transferred to a cleaning tank filled with deionized water, and ultrasonic-assisted cleaning is performed. After the cleaning is completed, the microspheres are separated from the cleaning solution by filtration, and then gently blown dry with clean nitrogen; S3, taking 27.5 kg of poly (N-isopropylacrylamide) and dispersing it in 100 kg of water to form a solution, re-dispersing the hollow glass microspheres that have been preliminarily washed and dried in 400 kg of a 40 wt% methanol aqueous solution, and adding the poly (N-isopropylacrylamide) aqueous solution at a slow speed and stirring to ensure that the poly (N-isopropylacrylamide) can be evenly dispersed and fully contact the surface of the microspheres modified by the fluorinated acrylate, controlling the temperature to 15° C. to promote further polymerization or adsorption of the poly (N-isopropylacrylamide) on the surface of the microspheres, and controlling the heat preservation reaction time to 2.5 h; After the reaction is completed, the mixed solution is heated to room temperature and filtered to separate the modified hollow glass microspheres. Finally, the microspheres are thoroughly washed, dried and sieved to remove residual solvents and unreacted polymers to obtain the final product hollow glass microspheres.

[0032] Preparation Example 2 A hollow glass microsphere is prepared by surface modification of hollow glass microspheres with fluorinated acrylate and poly (N-isopropylacrylamide). The difference from Preparation Example 1 is that the feeding ratio of the hollow glass microspheres to the fluorinated acrylate and poly (N-isopropylacrylamide) is different, that is, the mass ratio is 1:0.24:0.55. The specific situation is shown in the table below. Components Feeding amount (kg) Hollow glass microspheres 50 Fluorinated acrylate 12 Poly (N-isopropylacrylamide) 27.5

[0033] Preparation Example 3 A hollow glass microsphere is prepared by surface modification of hollow glass microspheres with fluorinated acrylate and poly (N-isopropylacrylamide). The difference from Preparation Example 1 is that the feeding ratio of the hollow glass microspheres to the fluorinated acrylate and poly (N-isopropylacrylamide) is different, that is, the mass ratio is 1:0.26:0.55. The specific situation is shown in the table below. Components Feeding amount (kg) Hollow glass microspheres 50 Fluorinated acrylate 13 Poly (N-isopropylacrylamide) 27.5

[0034] Preparation Example 4 A hollow glass microsphere is prepared by surface modification of hollow glass microspheres with fluorinated acrylate and poly (N-isopropylacrylamide). The difference from Preparation Example 1 is that the feeding ratio of the hollow glass microspheres to the fluorinated acrylate and poly (N-isopropylacrylamide) is different, that is, the mass ratio is 1:0.26:0.51. The specific situation is shown in the table below. Components Feeding amount (kg) Hollow glass microspheres 50 Fluorinated acrylate 13 Poly (N-isopropylacrylamide) 25.5

[0035] Preparation Example 5 A hollow glass microsphere is prepared by surface modification of hollow glass microspheres with fluorinated acrylate and poly (N-isopropylacrylamide). The difference from Preparation Example 1 is that the feeding ratio of the hollow glass microspheres to the fluorinated acrylate and poly (N-isopropylacrylamide) is different, that is, the mass ratio is 1:0.26:0.53. The specific situation is shown in the table below. Components Feeding amount (kg) Hollow glass microspheres 50 Fluorinated acrylate 13 Poly (N-isopropylacrylamide) 26.5

[0036] Preparation Example 6 A hollow glass microsphere is prepared by surface modification of hollow glass microspheres with fluorinated acrylate and poly (N-isopropylacrylamide), and the difference from Preparation Example 1 is that the hollow glass microspheres are selected from 3M TM Hollow glass microsphere S15. Example

[0037] Example 1 An aerogel-based anti-condensation coating, the raw material components and their amounts are shown in the following table: Components Content(kg) Deionized water 30 Hydroxyethyl methylcellulose 1 Powder 10 Lotion 35 Aerogel 3 Hollow glass beads 20 Additives 1 The powder is composed of carbonate powder and silicate powder, with a mass composition ratio of 40%:60%, which are respectively from Ningbo Luofei Nanotechnology's nano calcium LF-CaCO3-N80 and Yuejiang brand 1250 mesh ultrafine calcined kaolin; The cellulose was hydroxyethyl methyl cellulose, which was from Jiangsu Bosite Chemical; The emulsion is composed of tert-acrylic emulsion and styrene-acrylic emulsion, with a mass composition ratio of 33%:67%, which come from Shandong Baoda PD-9A tert-acrylic emulsion and Jiangsu Shengda SD-588 nano-styrene-acrylic emulsion respectively; The additives are composed of dispersants, defoamers and film-forming additives, with a mass composition ratio of 40%:40%:20%, which are from Maier Chemical HY-1010A, FOAM 235S and Eastman TEXANOL (alcohol ester 12); Aerogel is silica aerogel, which comes from Yantuo YTAP-Y10M.

[0038] The above-mentioned method for preparing an aerogel-based anti-condensation coating specifically comprises the following steps: Add cellulose to deionized water, stir at 1500 rpm for 0.2 h to fully dissolve it, then add additives and powder, reduce the speed to 800 rpm after uniform dispersion, add emulsion, and finally add aerogel and glass microbeads prepared in Preparation Example 1, and continue stirring for 0.6 h to obtain the product.

[0039] The performance of the aerogel-based anti-condensation coating prepared in Example 1 was tested according to the aforementioned standards, and the results are shown in the table below.

[0040] It can be seen from the above table that the aerogel-based anti-condensation coating prepared in Example 1 has an initial dew point of 81 min and a condensation amount of 2.6 g under the aforementioned test conditions. Due to the long initial dew point time and small condensation amount, it shows that it has good anti-condensation performance, which makes the coating have broad application prospects in related fields.

[0041] Analyzing the reasons, it may be: Aerogel, especially silica aerogel, is famous for its extremely high porosity, extremely low density and excellent thermal insulation performance. Adding aerogel to the coating can significantly reduce the thermal conductivity of the coating, effectively block heat transfer, reduce the temperature difference between the coating surface and the surrounding environment, and thus delay the occurrence of condensation. Hollow glass microspheres contain tiny bubbles inside, which also have excellent thermal insulation properties. They can further reduce the thermal conductivity efficiency of the coating, and work synergistically with aerogel to enhance the overall thermal insulation effect of the coating; The powder is a mixture of carbonate powder (such as nano calcium) and silicate powder (such as ultrafine calcined kaolin) in a certain proportion. This ratio may help to improve the film-forming properties of the coating, enhance the mechanical strength and weather resistance of the coating, and also help to adjust the pore structure of the coating and improve the anti-condensation effect. The emulsion is a mixture of tert-acrylic emulsion and styrene-acrylic emulsion. They both have excellent film-forming properties and water resistance, and can form a continuous and dense coating film. A reasonable ratio may help the emulsion to be better dispersed in the coating system and improve the overall performance and stability of the coating.

[0042] Comparative Example 1 An aerogel-based anti-condensation coating, purchased from ALFY&ANFOE AC-S20.

[0043] Comparative Example 2 An anti-condensation coating, purchased from Ba Strontium Fluoride (Wuxi) New Material Ultra-microporous Nano Anti-condensation Coating SC180.

[0044] Comparative Example 3 An aerogel-based anti-condensation coating purchased from FIREBIRD AG aerogel insulation coating.

[0045] The performance tests were carried out on the coatings in Comparative Examples 1-3 according to the above standards, and the results are shown in the table below.

[0046] It can be seen from the performance test results of the coatings in Comparative Examples 1-3 in the above table that their initial dew points are 31-34 min, and the condensation amount is 6.08-11.92 g. The initial dew points are all over 30 min, which is relatively long. At the same time, the condensation amount is also >5 g, and the condensation amount control is not ideal. It can be seen that the anti-condensation performance is not as good as the aerogel-based anti-condensation coating prepared in Example 1.

[0047] Embodiment 2-6 An aerogel-based anti-condensation coating, whose raw material components and preparation method are the same as those in Example 1, except that the content of each component is different, as shown in the table below.

[0048] Example 7 An aerogel-based anti-condensation coating, the preparation method and component content of which are the same as those in Example 1, the only difference being that an equal amount of 3M TM The hollow glass microspheres S15 are used to replace the hollow glass microspheres prepared in Preparation Example 1.

[0049] Comparative Example 4 An aerogel-based anti-condensation coating, the preparation method and component content of which are the same as those of Example 1, the only difference being that the hollow glass microspheres, one of the raw material components, are not modified, that is, the hollow glass microspheres are ordinary commercially available 3M TM Hollow glass microsphere K15.

[0050] The coatings prepared in Examples 2-7 and Comparative Example 4 were subjected to performance tests according to the aforementioned standards, and the results are shown in the table below.

[0051] It can be seen from the above table that the aerogel-based anti-condensation coatings prepared by Examples 2-6 have an initial dew point of 77-94 min and a condensation amount of 2.22-2.64 g under the aforementioned test conditions. Among them, Example 6 has the longest initial dew point (94 min) and the least condensation amount (2.22 g), making it the most preferred embodiment.

[0052] The aerogel-based anti-condensation coatings prepared in Example 7 and Comparative Example 4 have initial dew points of 61 min and 59 min, respectively, and condensation amounts of 5.38 g and 5.44 g, respectively. The condensation amounts are both over 5 g, and the initial dew point time is also shortened. This may be because the hollow glass microspheres in Example 1 have undergone dual surface modification with fluorinated acrylate and poly (N-isopropylacrylamide). The introduction of fluorinated acrylate may enhance the hydrophobicity of the microsphere surface, while poly (N-isopropylacrylamide) may give the microspheres temperature responsiveness, making them show better anti-condensation effect within a specific temperature range. In contrast, the 3M TM Hollow glass microsphere S15 has not been modified in any way, so the anti-condensation performance shows a downward trend from the test results; In addition, in Comparative Example 4, unmodified ordinary commercially available 3M TM The performance of hollow glass microsphere K15 is also inferior to that of the coating prepared in Example 1 according to the test results.

[0053] Examples 8-12 An aerogel-based anti-condensation coating, whose preparation method and component content are the same as those in Example 1, the only difference is that the hollow glass microspheres, one of the raw material components, come from different sources. The specific details are shown in the table below. Group Hollow glass microspheres source Example 1 Prepared from Preparation Example 1 Example 8 Prepared from Preparation Example 2 Example 9 Prepared from Preparation Example 3 Example 10 Prepared by Preparation Example 4 Embodiment 11 Prepared from Preparation Example 5 Example 12 Prepared from Preparation Example 6

[0054] The coatings prepared in Examples 8-12 were subjected to performance tests according to the aforementioned standards, and the results are shown in the table below.

[0055] It can be seen from the above table that the aerogel-based anti-condensation coatings prepared in Examples 8-11 have an initial dew point of 79-83 min and a condensation amount of 2.69-2.82 g under the aforementioned test conditions. Compared with the aerogel-based anti-condensation coating prepared in Example 1, the condensation amount increases slightly. In the test results of Example 9, the initial dew point is maintained at 83 min, which is even slightly better than that of Example 1. Taking all factors into consideration, Example 1 is the most preferred example. It can be seen that during the preparation of hollow glass microspheres, when the feeding ratio of hollow glass microspheres to fluorinated acrylate and poly (N-isopropylacrylamide) is 1:0.25:0.55, the hollow glass microspheres thus prepared can be used as one of the raw materials for preparing aerogel-based anti-condensation coatings, and can obtain the best anti-condensation performance.

[0056] As for Example 12, it uses 3M TM Hollow glass microsphere S15 to replace 3M TMHollow glass microspheres K15 are modified. Since different types of hollow glass microspheres (such as K15 and S15) may have differences in physical properties such as particle size, wall thickness, density, etc., these differences may affect the dispersion and stability of the microspheres in the coating and the interaction with other components of the coating, thereby affecting the anti-condensation performance of the coating. As shown in the above test results, the anti-condensation performance of Example 12 is greatly reduced compared with that of Example 1, with an initial dew point of 68min and a condensation amount of 4.85g, which shows that 3M TM Hollow glass microsphere K15 is preferred.

[0057] Embodiment 13 An aerogel-based anti-condensation coating, whose preparation method and component content are the same as those in Example 1, the only difference being that the use of powder as one of the raw material components used in the preparation is different. The powder is composed of carbonate powder and sulfate powder, and the mass composition ratio is 40%:60%, which are nano calcium LF-CaCO3-N80 from Ningbo Luofei Nano Technology and Guangdong Yuanlei "YLFT" brand 1250 mesh ultrafine barium sulfate.

[0058] Embodiment 14 An aerogel-based anti-condensation coating, whose preparation method and component content are the same as those in Example 1, the only difference being that the use of powder as one of the raw material components used in the preparation is different, and the powder is composed of carbonate powder, silicate powder, sulfate powder, metal and oxide powder, and special functional powder, and the mass composition ratio is 20%:20%:20%:20%:20%, respectively from Ningbo Luofei Nanotechnology's nano calcium LF-CaCO3-N80, Yuejiang brand 1250 mesh ultrafine calcined kaolin, Guangdong Yuanlei "YLFT" brand 1250 mesh ultrafine barium sulfate, Japan Daming Chemical TM-UF alumina powder, and ultrafine perlite powder YF-400.

[0059] Embodiment 15 An aerogel-based anti-condensation coating, whose preparation method and component content are the same as those in Example 1, the only difference being that the use of powder as one of the raw material components used in the preparation is different. The powder is composed of carbonate powder, silicate powder and sulfate powder, and the mass composition ratio is 40%:30%:30%, which are respectively from nano calcium LF-CaCO3-N80 of Ningbo Luofei Nanotechnology, Yuejiang brand 1250 mesh ultrafine calcined kaolin and Guangdong Yuanlei "YLFT" brand 1250 mesh ultrafine barium sulfate.

[0060] Example 16 An aerogel-based anti-condensation coating, the preparation method and component content of which are the same as those in Example 1, the only difference being that the cellulose used as one of the raw material components in the preparation is different, namely, hydroxypropyl methylcellulose from KemoxHPMC.

[0061] Embodiment 17 An aerogel-based anti-condensation coating, whose preparation method and component content are the same as those in Example 1, the only difference being that the use of cellulose, one of the raw material components used in the preparation, is different. The coating is composed of hydroxypropyl methylcellulose, hydroxyethyl methylcellulose, methyl cellulose, hydroxyethyl cellulose, and carboxymethyl cellulose in a mass composition ratio of 20%:20%:20%:20%:20%, which are respectively from Kemox HPMC, Jiangsu Bost Chemical, Hubei Guangao Biotechnology, Kemox HECBF4009, and Wuhan Jixinyibang Biology.

[0062] Embodiment 18 An aerogel-based anti-condensation coating, whose preparation method and component content are the same as those in Example 1, the only difference being that the emulsion used in one of the raw material components used in the preparation is different, and is composed of acrylic emulsion and styrene-acrylic emulsion, with a mass composition ratio of 33%:67%, which are respectively from Baolijia BLJ-938 and Jiangsu Shengda SD-588 nano styrene-acrylic emulsion.

[0063] Embodiment 19 An aerogel-based anti-condensation coating, whose preparation method and component content are the same as those in Example 1, the only difference being that the use of an emulsion as one of the raw material components used in the preparation is different, and the emulsion is composed of tert-acrylic emulsion, acrylic emulsion and styrene-acrylic emulsion, with a mass composition ratio of 33%:33%:34%, which are respectively from Shandong Baoda PD-9A tert-acrylic emulsion, Baolijia BLJ-938 acrylic emulsion, and Jiangsu Shengda SD-588 nano-styrene-acrylic emulsion.

[0064] Embodiment 20 An aerogel-based anti-condensation coating, the preparation method and component content of which are the same as those in Example 1, the only difference being that the emulsion used as one of the raw material components is used differently, and is composed of styrene acrylic emulsion, acrylic emulsion, silicone acrylic emulsion, fluorocarbon emulsion, chloroform emulsion, silicone resin emulsion, water-based polyurethane resin emulsion, and tert-propylene emulsion, and the mass composition ratio is equal, namely 12.5%: 12.5%: 12.5%: 12.5%: 12.5%: 12.5%: 12.5%, respectively, which are from Jiangsu Shengda SD-588 nano styrene acrylic emulsion, Baolijia BLJ-938 acrylic emulsion, SD-5281 nano silicone acrylic emulsion, Ruifeng RF-101 water-based single-component fluorocarbon emulsion, Wuhan Jiye Shenghua JYS1541 chloroform emulsion, DOWSIL TM 8016 Waterborne Resin, Shandong Baoda PD-9A tert-acrylic emulsion.

[0065] Embodiment 21 An aerogel-based anti-condensation coating, whose preparation method and component content are the same as those in Example 1, the only difference being that the use of aerogel, one of the raw material components used in the preparation, is different. The aerogel is prepared by dispersing aerogel powder material in water. The aerogel powder material is alumina aerogel from Hunan Ronglan Al2O3 aerogel.

[0066] Embodiment 22 An aerogel-based anti-condensation coating, whose preparation method and component content are the same as those in Example 1, the only difference being that the use of aerogel, one of the raw material components used in the preparation, is different. The aerogel is prepared by dispersing aerogel powder material in water. The aerogel powder material is a graphene-titanium dioxide composite aerogel purchased from Xi'an Ruixi Biological R-QD-0508.

[0067] Embodiment 23 An aerogel-based anti-condensation coating, whose preparation method and component content are the same as those in Example 1, the only difference being that the use of aerogel, one of the raw material components used in the preparation, is different. The aerogel is prepared by dispersing aerogel powder material in water. The aerogel powder material is a silica-alumina composite aerogel from Xi'an Ruixi Biological R-MCS-348.

[0068] The coatings prepared in Examples 13-23 were subjected to performance tests according to the aforementioned standards. The results are shown in the table below.

[0069] It can be seen from the above table that the aerogel-based anti-condensation coatings prepared in Examples 13-23 have an initial dew point of 74-80 min and a condensation amount of 2.62-3.31 g under the aforementioned test conditions. Compared with the aerogel-based anti-condensation coating prepared in Example 1, the initial dew point time (min) is advanced by 1.23-8.64%, and the condensation amount (g) is increased by 0.8-27.3%. Although these examples have some adjustments in the composition of raw materials such as powders, cellulose, emulsions or aerogels, the anti-condensation performance of the aerogel-based anti-condensation coatings prepared is generally weakened compared to Example 1.

[0070] In Examples 13 and 15, sulfate powder (such as barium sulfate) is added to the powder, which may change the surface energy and hydrophilicity of the coating, thereby affecting the anti-condensation performance. Sulfate powder may not be as effective as silicate powder in preventing condensation; In Example 14, more types of powders (carbonate series, silicate series, sulfate series, metal and oxide series, special functional powders) are used. Although this increases the complexity and functionality of the coating, it may also lead to interactions between powders that are not conducive to anti-condensation performance. The particle size, shape and surface properties of the powder will also affect its anti-condensation effect. Therefore, powders from different sources and types may differ in these aspects.

[0071] Different types of cellulose are used in Examples 16 and 17, and the hygroscopicity, water retention and film-forming properties of these celluloses may be different, thus affecting the anti-condensation performance of the coating. Mixing and using multiple celluloses (such as Example 17) may not be conducive to forming a uniform and dense coating, thereby affecting the anti-condensation effect.

[0072] In Examples 18 to 20, the types and proportions of the emulsions were changed. Different emulsions have differences in film-forming properties, water resistance, air permeability, etc., and these properties will affect the anti-condensation effect of the coating. For example, although styrene-acrylic emulsions and acrylic emulsions are commonly used and have good performance, when mixed with other emulsions (such as silicone-acrylic emulsions and fluorocarbon emulsions), the overall anti-condensation performance may decrease due to compatibility issues or performance differences.

[0073] In Examples 21 to 23, the types of aerogels have changed. Different types of aerogels differ in pore structure, specific surface area, adsorption performance, etc., which will affect their anti-condensation effects. For example, alumina aerogel, graphene-titania composite aerogel and silica-alumina composite aerogel may differ in thermal conductivity, hygroscopicity and air permeability, thereby affecting the anti-condensation performance of the coating.

[0074] The above are all modifications without creative contribution or solutions that obviously constitute technical inspiration that can be made to the present embodiment as needed by technical personnel in this field after reading this specification, but they should be protected by patent law as long as they are within the scope of the claims of this application.

Claims

1. An aerogel-based anti-condensation coating, characterized in that: Each component is measured by weight percentage, including: Deionized water 30-45% Cellulose 0.1-1.0% Powder 5-10% Emulsion 25-35% Aerogel 0.5-3.0% Hollow glass beads 15-30% Additives 1-2%.

2. The aerogel-based anti-condensation coating according to claim 1, characterized in that: Each component is measured by weight percentage, including: Deionized water 30-35% Cellulose 0.1-0.5% Powder 5-10% Emulsion 25-30% Aerogel 1.5-3.0% Hollow glass beads 15-25% Additives 1-2%.

3. The aerogel-based anti-condensation coating according to claim 2, characterized in that: Each component is measured by weight percentage, including: Deionized water 35% Cellulose 0.5% Powder 5% Lotion 30% Aerogel 2.5% Hollow glass beads 25% Additive 2%.

4. The aerogel-based anti-condensation coating according to any one of claims 1 to 3, characterized in that: The hollow glass microspheres are hollow glass microspheres obtained by surface modification with fluorinated acrylate and poly-N-isopropylacrylamide.

5. The aerogel-based anti-condensation coating according to claim 4, characterized in that: The specific preparation steps of the hollow glass microsphere modification include: S1. placing hollow glass microspheres in a plasma reactor and introducing fluorinated acrylate vapor. Under the action of plasma, monomer molecules are excited and polymerized, and deposited on the surface of the microspheres; S2. After the surface polymerization deposition of the fluorinated acrylate is completed, the modified hollow glass microspheres are taken out from the plasma reactor and preliminarily cleaned to remove unreacted monomers and byproducts on the surface; S3, then re-dispersing the microbeads in an aqueous solution of methanol to form a stable suspension, then adding a certain amount of poly (N-isopropylacrylamide) solution to the suspension to ensure that the poly (N-isopropylacrylamide) can be evenly dispersed and contacted with the surface of the microbeads modified by the fluorinated acrylate to form a mixed solution, then controlling the temperature of the mixed solution and continuously stirring it, keeping the temperature for reaction for 2.5-3 hours, and then post-treating it to obtain; The feeding ratio of the hollow glass microspheres to the fluorinated acrylate and poly (N-isopropylacrylamide) is 1:(0.24-0.26):(0.51-0.55) by mass ratio.

6. The aerogel-based anti-condensation coating according to any one of claims 1 to 3, characterized in that: The cellulose is one or more of hydroxypropyl methylcellulose, hydroxyethyl methylcellulose, methylcellulose, hydroxyethyl cellulose and carboxymethyl cellulose.

7. The aerogel-based anti-condensation coating according to any one of claims 1 to 3, characterized in that: The powder is one or more of carbonate powder, silicate powder, sulfate powder, metal and oxide powder, and special functional powder.

8. The aerogel-based anti-condensation coating according to any one of claims 1 to 3, characterized in that: The emulsion is one or more of styrene acrylic emulsion, acrylic emulsion, silicone acrylic emulsion, fluorocarbon emulsion, chloroform emulsion, organic silicone resin emulsion, waterborne polyurethane resin emulsion and tert-acrylic emulsion.

9. The aerogel-based anti-condensation coating according to any one of claims 1 to 3, characterized in that: The aerogel is prepared by dispersing aerogel powder material in water, wherein the specific surface area of ​​the aerogel powder material is 500-800m 2 / g, a density of 0.08-0.1g / ml, a particle size of 0.01-1mm, and at least one of silica aerogel, alumina aerogel, graphene-titania gel, and silica-alumina composite aerogel.

10. The aerogel-based anti-condensation coating according to any one of claims 1 to 3, characterized in that: The auxiliary agent includes one or more of a dispersant, a wetting agent, a defoaming agent, a pH regulator, and a film-forming auxiliary agent.

Citation Information

Cited By

  • Odor-free temperature-sensitive coating and preparation method thereof

    CN120209659A

  • Anti-condensation coating containing aerogel and preparation process of anti-condensation coating

    CN121064682A

  • Anti-fogging coating containing aerogel and process for its preparation

    CN121064682B

  • Anti-condensation coating based on nano aerogel and preparation method of anti-condensation coating

    CN121673931A

  • Anti-fogging coating based on nano-aerogel and preparation method thereof

    CN121673931B